Current Breast Feeding Practices: Are these Compliant with WHO Recommendations? - Saadat Naqvi, Warda Ali Naqvi, Nabeela Waheed, Khansa Iqbal, Nayab Nadeem, Syeda Sumbul Zahra Zaidi, Saadat Naqvi, Warda Ali Naqvi, Nabeela Waheed, Khansa Iqbal, Nayab Nadeem, Syeda Sumbul Zahra Zaidi (Journal of Rawalpindi Medical College, 2017)
Background: To study the current breast feeding practices in mothers who underwent caesarean section and to what extent these comply with the world health organization (WHO) recommendations. Methods: This cross-sectional study was based on a survey conducted on women delivered by caesarean section .Proforma built for the survey was completed by interviewing of the subjects. Frequencies of the observations were described as means and percentages. Pearson chi square test was used to find association between early initiation of breast feeding (EIBF) and independent variables. Binary logistic regression was used to investigate association of factors with EIBF independently. Results: EIBF was found in 15% of infant-mother pairs. All other mothers-infant pairs (85 %) started early breast feeding(EBF) i.e. breast feeding (BF_ between 2 to 24 hours after delivery. Majority of infants were given a drink, other than breast milk, within 24 after delivery. Counselling or assistance for EIBF or exclusive breast feeding was not provided by healthcare workers to any mother. Main factor significantly associated with initiating breastfeeding during 1st hour after caesarean delivery was attendant’s awareness about recommendation of EIBF. Conclusion: There is poor adherence to WHO recommendations for early initiation of breast feeding i.e. during 1st hour after birth. However, EBF was found in all mothers who did not start EIBF